Effect of Biodegradable and Polypropylene Film Packaging on the Safety Profile of Jelly Marmalade - Pesterev Mikhail A.; Rudenko Oxana S.; Kondrat’ev Nikolay B.; Bazhenova Alla E.; Usachev Ivan S. (Техника и технология пищевых производств)
Introduction. Waste management and poorly degradable polymer packaging are one of the main environmental issues. Biodegradable materials based on a composition of native and modified starches can solve the problem of polymer waste in food packaging. They are environmentally friendly and harmless during decomposition. However, the barrier properties of biodegradable films still remain understudied. Study objects and methods. The research featured the safety profile of gelatinous confectionery products during storage in biodegradable and polypropylene films. It focused on moisture transfer and microbiota growth in glazed jelly marmalade. The first sample was wrapped in oriented polypropylene film (40 microns), while the other sample was packaged in a biodegradable film (50 microns). A set of experiments was conducted to measure the mass fraction of moisture, water activity, fatty acid composition of the fat fraction of the glaze, active acidity, microbiological parameters, and lipase activity during storage. Results and discussion. The activity of water during storage remained the same. The specific rate of moisture transfer for the polypropylene film sample was approximately 1.4 times higher than for the biodegradable sample. It equaled 1.16×10–6 g/m2·s for the polypropylene film sample and 0.83×10–6 g/m2·s for the biodegradable sample. The dynamics of growth of QMAFAnM, mold, and yeast was the same in both samples; it did not exceed the regulated indicators of microbiological safety after 12 weeks of storage. The lipase activity of the glazed marmalade samples packed in the polymer film did not increase during storage. Replacing the polypropylene film with a biodegradable film did not significantly affect the safety profile of confectionery products. Conclusion. Research results confirmed the possibility of using a biodegradable film for packaging confectionery products.